Current concepts and outcomes in cemented femoral stem design and cementation techniques: the argument for a new classification system. Issue 4 (2nd April 2020) - Cassar-Gheiti, Adrian J.; McColgan, Rosie; Kelly, Martin; Cassar-Gheiti, Theresa M.; Kenny, Paddy; Murphy, Colin G.
Abstract : Cemented implant fixation design principles have evolved since the 1950s, and various femoral stem designs are currently in use to provide a stable construct between the implant–cement and cement–bone interfaces. Cemented stems have classically been classified into two broad categories: taper slip or force closed, and composite beams or shaped closed designs. While these simplifications are acceptable general categories, there are other important surgical details that need to be taken into consideration such as different broaching techniques, cementing techniques and mantle thickness. With the evolution of cemented implants, the introduction of newer implants which have hybrid properties, and the use of different broaching techniques, the classification of a very heterogenous group of implants into simple binary categories becomes increasingly difficult. A more comprehensive classification system would aid in comparison of results and better understanding of the implants' biomechanics. We review these differing stem designs, their respective cementing techniques and geometries. We then propose a simple four-part classification system and summarize the long-term outcomes and international registry data for each respective type of cemented prosthesis. Cite this article: EFORT Open Rev 2020;5:241-252. DOI: 10.1302/2058-5241.5.190034